Wind Turbine Syndrome A Communicated Disease - Chapman, Simon (Public and Social Policy, 2017)
In Wind Turbine Syndrome: A Communicated Disease, Simon Chapman and Fiona Crichton explore the claims and tactics of the anti-windfarm movement, examine the scientific evidence, and consider how best to respond to anti-windfarm arguments.